A Mixed-Methods Analysis of Mobile ACT Responses From Two Cohorts - Hoel, Sydney; Victory, Amanda; Sagorac Gruichich, Tijana; Stowe, Zachary N.; McInnis, Melvin G.; Cochran, Amy; Thomas, Emily B. K. (Frontiers in Digital Health, 2022)
Background: Mobile transdiagnostic therapies offer a solution to the challenges of limited access to psychological care. However, it is unclear if individuals can actively synthesize and adopt concepts and skills via an app without clinician support. Aims: The present study measured comprehension of and engagement with a mobile acceptance and commitment therapy (ACT) intervention in two independent cohorts. Authors hypothesized that participants would recognize that behaviors can be flexible in form and function and respond in an ACT process-aligned manner. Methods: Mixed-methods analyses were performed on open-ended responses collected from initial participants (n=49) in two parallel micro-randomized trials with: 1) first-generation college students (FGCSs) (n=25) from a four-year public research university and 2) individuals diagnosed with bipolar disorder (BP) (n=24). Twice each day over six weeks, participants responded to questions about mood and behavior, after which they had a 50-50 chance of receiving an ACT-based intervention. Participants identified current behavior and categorized behavior as values-based or avoidant. Interventions were selected randomly from 84 possible prompts, each targeting one ACT process: engagement with values, openness to internal experiences, or self-awareness. Participants were randomly assigned to either exploratory (10 FGCS, 9 BP) or confirmatory (15 FGCS, 15 BP) groups for analyses. Responses from the exploratory group were used to inductively derive a qualitative coding system. This system was used to code responses in the confirmatory group. Coded confirmatory data were used for final analyses. Results: The median participant in both cohorts submitted a non-blank response 100% of the time. Intervention responses from the median participant aligned with the target ACT process 96% of the time (FGCS) and 91% of the time (BP), and current behavior was labelled as values-based 70% (FGCS) and 85% (BP) of the time. Participants labeled similar behaviors flexibly as either values-based or avoidant in different contexts. Dominant themes were needs-based behaviors, interpersonal and family relationships, education, and time as a cost. Conclusions: Both cohorts were engaged with the app, as demonstrated by responses that aligned with ACT processes. This suggests that participants had some level of understanding that behavior can be flexible in form and function.